1998
DOI: 10.1007/pl00003468
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics of whiplash injury

Abstract: The article reports a new hypothesis of whiplash injury based on a series of experimental studies using isolated human cadaveric specimens. Although the clinical symptoms of whiplash are widely known, the understanding of the underlying injury mechanism is poor. The prevailing view of neck-hyper-extension as the essential injury mechanisms was not supported by recent experiments. In a series of experiments using eight human cadaveric specimens which underwent experimental stepwise whiplash acceleration from 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…[31][32][33] Nevertheless, these experiments can only be an approach to reality because the influence of muscular tonicity, for example, cannot be simulated. Results of animal studies in which transient pressure pulses in the cervical spinal canal during experimental neck trauma were recorded indicate that WAD could also appear due to other factors, such as involvement of the cervical spinal nerve root region.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] Nevertheless, these experiments can only be an approach to reality because the influence of muscular tonicity, for example, cannot be simulated. Results of animal studies in which transient pressure pulses in the cervical spinal canal during experimental neck trauma were recorded indicate that WAD could also appear due to other factors, such as involvement of the cervical spinal nerve root region.…”
Section: Discussionmentioning
confidence: 99%
“…Biomechanical data about loads and deformations of the cervical spine during rear-end collisions are available from numerous trials with volunteers [2,3] and some in vitro tests with cadaveric cervical spine specimens [4,7,15,16,25]. Panjabi's in vitro experiment in particular [16] indicated that rear-end collisions might cause functional injury to the lower cervical spine, but not to the upper segments. However, from a clinical point of view, about 20% of all patients suffer from symptoms in the upper cervical spine.…”
Section: Introductionmentioning
confidence: 99%
“…In 1971, McKenzie and Williams, 47 using a mathematical model of the head, neck, and torso, predicted that some degree of initial flexion of the head relative to the torso occurs before rapid hyperextension. Later, Grauer et al 48 and Panjabi et al, 49 using cadaveric cervical spines on a benchtop model concluded that in whiplash, the neck forms an S-shaped curvature with lower-level hyperextension and upper level flexion followed by a subsequent C-shaped curvature with extension of the entire cervical spine. In 1999, Kaneoka et al, 50 using healthy volunteers on a sled apparatus, observed that C5-C6 extended before the upper vertebrae in the early phase of whiplash.…”
Section: Discussionmentioning
confidence: 97%